Desenvolvimento de peneiras moleculares mesoporosas do tipo MCM-41 e MCM-48 impregnadas com aminas para utilização na adsorção de CO2 - Oliveira, Thiago Gallo de (2012)
The significant increase of carbon dioxide emissions in the atmosphere comes intensifying the global warming. The search for energetic source that turn emission down is of great importance, as well as the use of complementary actions like dioxide carbon capture process of the main emissions sources. From among some processes already very well-known industrially highlights chemical absorption with alkanolamine, which shows some disadvantages in being costly and generate waste derived from recovery. The use gas-solid selective in carbon dioxide adsorption has very advantages over absorption liquid amine such as easy handling without risks to the environment and recovering of adsorbent material, being possible to use industries plants with continuous flux. In this context were synthesized through hydrothermal method two materials of family M41S of type MCM-41 and MCM-48. Then the materials were impregnated with ethylenediamine by wet impregnation method. These materials were used for the carbon dioxide adsorption process and were characterized by several physic-chemical techniques. The powder X-ray diffraction patterns of the samples showed all peaks characteristics of MCM-41 and MCM-48 before and after impregnation with amines. The absorption spectrum in the infrared region showed bands due to Si-O and O-Si-O bonds in all materials and N-H bonds due to presence of amine in the supports after impregnation process. The thermogravimetric curves showed that stability of material containing amines is up to 100 °C. The materials showed N2 adsorption isotherms type IV, some with hysteresis type H1 and high surfaces areas (over 1000 m2 g-1). Carbon dioxide capture tests in flux system and atmosphere pressure showed significant drawbacks in the capture capacities of carbon dioxide for the materials impregnated with ethylenediamine in comparison to the values obtained with the MCM-41 and MCM-48 supports alone. Tests with closed system and pressure variation in the range of 0.5 to 30 bar allowed the construction of the isotherms to prepared materials of which were fitted using the Langmuir model. The results showed that the samples of MCM-41 and MCM-48 without impregnation are favorable for applications where high pressures are required.